Infrastructure-led development and the peri-urban question: Furthering crossover comparisons. (June 2022) - Kanai, J Miguel; Schindler, Seth
Contemporary development policy portrays enhanced connectivity as the key to fostering economic growth in lagging regions. This global policy consensus and consequent infrastructure scramble have resulted in a proliferation of new urban spaces. These are dispersed, fragmentary and often unrecognised as urban by projects and plans centred on large-scale connective infrastructures to integrate remote regions into circuits of capital. Whilst our understanding of infrastructure-led development is informed by critical engagements with planetary urbanisation, global infrastructure and logistics, this position paper seeks to reconcile political economy analyses with situated studies closer to lived forms of heterogeneous precariousness in emerging urban worlds. Addressing recent debates that frame these bodies of scholarship as antagonistic, we emphasise the supplementarity of perspectives from within and beyond urban studies. This pluralism can be practised through comparisons that will (i) trace the geo-economic relationality of mega-infrastructures, which conditions directly and indirectly their planning, financing, construction and management, and (simultaneously or independently) (ii) examine difference in the diverse experiences of and responses to emergent infrastructural urbanisms of precarity. The article shows that genetic and generative comparisons can inform a research agenda on (peri-)urban precariousness, engaging policies with unmistakable global moorings but complex multi-scalar politics, diverging outcomes and situated resistances and appropriations.